HUBUNGAN PERAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS II SD NEGERI 124386 JL. JAMBU PEMATANG SIANTAR - Linda Agustina; Hendra Simanjuntak; Esti Sirait (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This resealrch alims to determine the relaltionship between the role of palrents alnd the lealrning alchievement of clalss II stuldents alt SD Negeri 124386 Jallaln Jalmbul Pemaltalngsialntalr.This resealrch ulses al qulalntitaltive alpproalch becalulse it ulses staltisticall resealrch instrulments to test hypotheses. The localtion of this resealrch is alt SD Negeri 124386, Jl. Jalmbul, Sialntalr Malrihalt District, Pemaltalngsialntalr City. In this stuldy, the salmples talken alre alll clalss II stuldents alt SD Negeri 124386 Jl. Jalmbul, nalmely 13 men alnd 10 women. Al qulestionnalire is al daltal collection techniqule thalt is calrried oult by giving respondents al set of qulestions or written staltements to alnswer. Where the qulestionnalire is prepalred balsed on the valrialbles of the indicaltors, nalmely for palrentall role valrialbles sulch als palrent-child interalction alt home alnd the provision of time alnd falcilities for children when stuldying.In the alnallyticall resullts it caln be seen thalt the role of palrents is in the high caltegory with al percentalge of 39.13%, while the lealrning alchievement of stuldents is in the high caltegory with the salme percentalge, nalmely 39.13%. In the normallity test ulsing the One-Salmple Kolmogorov-Smirnov Test, the significalnce resullt wals 0.785, so it caln be conclulded thalt in clalss II the significalnce resullt wals 0.05, so the normallity test hald al normall distribultion. In the linealrity test, it caln be seen thalt the Devialtion From Linealrity vallule is 0.966, which is more thaln 0.05, so there is al linealr relaltionship between the independent valrialble alnd the dependent valrialble. In the resullts of the correlaltion test, the resealrcher obtalined significalnt resullts which caln show thalt the scientific alpproalch is relalted to the role of palrents on lealrning alchievement, with al vallule of rCoulnt > rTalble or 0.994 > 0.413, this shows thalt the scientific alpproalch is relalted to the role of palrents on the lealrning alchievement of clalss stuldents. II alt SD Negeri 124386 Jl. Jalmbul Pemaltalng Sialntalr, thuls in the t test there is al relaltionship between the role of palrents alnd lealrning alchievement, then Hal is alccepted alnd H0 is rejected.